Modeling of Electrocardiogram Signals Using Predefined Signature and Envelope Vector Sets. (28th January 2007) - Gürkan Gürkan, Hakan Hakan; Güz Güz, Ümit Ümit; Yarman Yarman, B. Sıddık B. Sıddık
Abstract : A novel method is proposed to model ECG signals by means of "predefined signature and envelope vector sets (PSEVS)." On a frame basis, an ECG signal is reconstructed by multiplying three model parameters, namely, predefined signature vector( PSV ) R, " "predefined envelope vector( PEV ) K, " and frame-scaling coefficient (FSC). All the PSVs and PEVs are labeled and stored in their respective sets to describe the signal in the reconstruction process. In this case, an ECG signal frame is modeled by means of the members of these sets labeled with indicesR andK and the frame-scaling coefficient, in the least mean square sense. The proposed method is assessed through the use of percentage root-mean-square difference (PRD) and visual inspection measures. Assessment results reveal that the proposed method provides significant data compression ratio (CR) with low-level PRD values while preserving diagnostic information. This fact significantly reduces the bandwidth of communication in telediagnosis operations.